Preliminary evaluation of heavy metal contamination and source identification in Kuala Lumpur SMART stormwater pond sediments using Pb isotopic signature - Alrabie, Nabeel Abdullah; Mohamat-Yusuff, Ferdaus; Hashim, Rohasliney; Zulkeflee, Zufarzaana; Amal, Mohammad Noor Azmai; Arshad, Aziz; Zulkifl, Syaizwan Zahmir; Wijaya, Anugrah Ricky; Masood, Najat; Abdullah Sani, Muhamad Shirwan (MDPI AG, 2021)
Uncontrolled urbanization and growing industrialization are major sources of pollutants that affect the urban stormwater quality and, therefore, the receiving aquatic environment. The concentrations of heavy metals (As, Cd, Cr, Cu, Fe, Ni, Pb, and Zn), and Pb isotope ratios in surface sediment samples obtained from SMART holding and storage ponds located in Kuala Lumpur were investigated using inductively coupled plasma-mass spectrometry (ICP-MS). The highest metal concentrations were found at the SMART holding pond (SHP), the first recipient of urban stormwater runoff from the SMART system catchment area. As, Cd, Pb, and Zn are the dominant metal contaminants in the sediments of both SMART ponds, with values exceeding the average shale values. According to contamination indices applied to evaluate the environmental risk caused by heavy metals, As had the highest values among the metals examined, denoting moderate contamination. Hence, it can frequently cause harmful effects on the sediment-living species. The Pb isotope ratios (206Pb/207Pb and 208Pb/207Pb) indicated that coal combustion was the foremost source of anthropogenic Pb in the sediments of both SMART ponds. The control of coal combustion and sites undergoing intensive human activities should be given priority in the foreseeable future.